Nanostructures for novel therapy synthesis, characterization and applications - Ficai, Denisa; Grumezescu, Alexandru Mihai (Amsterdam Elsevier, 2017)
Nanostructures for Novel Therapy: Synthesis, Characterization and Applications focuses on the fabrication and characterization of therapeutic nanostructures, in particular, synthesis, design, and in vitro and in vivo therapeutic evaluation. The chapters provide a cogent overview of recent therapeutic applications of nanostructured materials that includes applications of nanostructured materials for wound healing in plastic surgery and stem cell therapy. The book explores the promise for more effective therapy through the use of nanostructured materials, while also assessing the challenges their use might pose from both an economic and medicinal point of view. This innovative look at how nanostructured materials are used in therapeutics will be of great benefit to researchers, providing a greater understanding of the different ways nanomaterials could improve medical treatment, along with a discussion of the obstacles that need to be overcome in order to guarantee widespread availability.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nanostructures -- Therapeutic use; Nanomedicine; Electronic books